Getting Rid of the Usability/Security Trade-Off: A Behavioral Approach - Francesco Di Nocera; Giorgia Tempestini (Journal of Cybersecurity and Privacy, 2022)
The usability/security trade-off indicates the inversely proportional relationship that seems to exist between usability and security. The more secure the systems, the less usable they will be. On the contrary, more usable systems will be less secure. So far, attempts to reduce the gap between usability and security have been unsuccessful. In this paper, we offer a theoretical perspective to exploit this tradeoff rather than fight it, as well as a practical approach to the use of contextual improvements in system usability to reward secure behavior. The theoretical perspective, based on the concept of reinforcement, has been successfully applied to several domains, and there is no reason to believe that the cybersecurity domain will represent an exception. Although the purpose of this article is to devise a research agenda, we also provide an example based on a single-case study where we apply the rationale underlying our proposal in a laboratory experiment.